Where Women Are Gender & The 2017 Kenyan Elections - Nyabola, Nanjala; Pommerolle, Marie-Emmanuelle (Africae Studies, 2018)
While the drama of the complicated 2017 General election in Kenya unfolded and the clash between the patriarchs dominated the headlines, women were once again relegated to a secondary position in the public conversation. 'Flower girls'. 'Someone's Wife'. These are some of the terms used to describe Kenyan women in politics - as simply accompanying and supporting men rather than having complex identities and public lives of their own. Yet Kenyan women were present and active, pushing against layers of structural and physical gendered violence to claim space in the political arena. This collection captures some of the stories and experiences of women participating in the heated 2017 general election in Kenya in order to shed light on the nuances and complexities facing women who choose to enter electoral politics. From stories of rural women using traditional social networks to access political power, to young urban women defying expectations and confronting an electorate that was conditioned to ignore them, these stories not only highlight the problems that women face but also the ingenious ways they navigate the spaces that do exist. Kenyan women are present and active in politics and this book works to see and understand where they are.